Children's attitudes toward interaction with an unfamiliar peer with complex communication needs: comparing high- and low-technology devices. (1st October 2016) - Dada, Shakila; Horn, Tenille; Samuels, Alecia; Schlosser, Ralf W.
Abstract: This study examined the attitudes of children with typical development towards an unfamiliar peer with complex communication needs using augmentative and alternative communication (AAC) systems. Specifically, the study aimed to compare attitudes when the peer used mobile technology (i.e., iPad © 1 ) with an AAC-specific application (Proloquo2Go™ 2 ) versus a low-technology communication board. A within-group crossover design was utilized involving 78 children. Half of the participants (i.e., Group 1) viewed Video 1 of an unfamiliar peer with complex communication needs in a scripted communication interaction using an iPad with Proloquo2Go followed by Video 2 of the same interaction using a communication board. The other half of the participants (Group 2) viewed these videos in the reverse sequence. The Communication Aid/Device Attitudinal Questionnaire (CADAQ) was completed after watching each video. Results indicated that both groups were more positive towards Video 1 (iPad with Prologuo2Go) on certain dimensions of the CADAQ. The results are discussed and recommendations for future research provided.